2014
DOI: 10.1172/jci69557
|View full text |Cite
|
Sign up to set email alerts
|

KLF4-dependent epigenetic remodeling modulates podocyte phenotypes and attenuates proteinuria

Abstract: The transcription factor Kruppel-like factor 4 (KLF4) has the ability, along with other factors, to reprogram somatic cells into induced pluripotent stem (iPS) cells. Here, we determined that KLF4 is expressed in kidney glomerular podocytes and is decreased in both animal models and humans exhibiting a proteinuric. Transient restoration of KLF4 expression in podocytes of diseased glomeruli in vivo, either by gene transfer or transgenic expression, resulted in a sustained increase in nephrin expression and a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 54 publications
4
122
0
Order By: Relevance
“…The transcription of PODXL has previously been reported to be positively regulated by WT1 and SP1 [51,52], but negatively by p53 [53]. In agreement with KLF4 and WT1 regulation of PODXL, WT1 and KLF4 are also critical for podocyte functions [54,55]. Immunohistochemistry of H1-teratoma with antibody 3D3, and human OCT4 antibody.…”
Section: Residual Podxlmentioning
confidence: 65%
“…The transcription of PODXL has previously been reported to be positively regulated by WT1 and SP1 [51,52], but negatively by p53 [53]. In agreement with KLF4 and WT1 regulation of PODXL, WT1 and KLF4 are also critical for podocyte functions [54,55]. Immunohistochemistry of H1-teratoma with antibody 3D3, and human OCT4 antibody.…”
Section: Residual Podxlmentioning
confidence: 65%
“…33,34 Klf4 in glomerular podocytes facilitates cell function and a reduction in proteinuria. 35 Here, we report that inverse expression of Klf5 and Klf4 was switched between soft and stiff matrices. Yes-associated protein 1 (YAP1)-transduced mechanical cues from matrix stiffness may regulate the inverse expression of Klf5 and Klf4, subsequently deciding the cellular fate.…”
mentioning
confidence: 84%
“…Interestingly, it was also reported that salutary benefits of glucocorticoids in the kidney are mediated by KLF15 . Furthermore, it was recently reported that transcriptional regulation of KLF6 enhances mitochondrial cytochrome oxidase activity in the setting of podocyte stress , and KLF4 increases the expression of genes involved in maintenance of the renal filtration barrier by reducing methylation in their promoter region (Hayashi et al, 2014). Finally, haploinsufficiency of Klf5 in collecting duct cells exacerbates the inflammatory response in murine models of kidney fibrosis (Fujiu et al, 2011).…”
Section: Klfs In Kidney Diseasementioning
confidence: 99%